1987
DOI: 10.1007/bf01412772
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of rotation and translation in hexagonal aggregates of extended chains

Abstract: Potential energy calculations have been made for hexane aggregates m the hexagonal arrangement as models of paraffin-like solids. As a part of the general energy hypersurface the feasibility of translation and rotation of extended chains in aggregate has been examined for various degrees of packing. The pure translation is favoured over the pure rotation at all interchain separations. The energy map of coupled rotation-translation motion has been developed for the intermediate degree of packing. The energy min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…From detailed analyses of the local and global orientational order, it is found that the formation of the global orientational order as well as the growth of the local ordered regions proceeds stepwise. The crystal structure of the rotator phase of n-alkanes, which are typical of short polymer chains with simple chemical structure, has been extensively studied by experiments [1][2][3][4][5][6][7][8][9], theoretical analyses [10,11], and computer simulations [12][13][14][15][16][17][18]. Several experimental techniques including x-ray diffraction [1][2][3][4], infrared and Raman spectroscopy [5,6], neutron scattering [7,8], and NMR [9] have been used to reveal interesting features of the molecular packing, intramolecular defects, and molecular motions in the rotator phase of n-alkanes.…”
Section: Susumu Fujiwara and Tetsuya Satomentioning
confidence: 99%
“…From detailed analyses of the local and global orientational order, it is found that the formation of the global orientational order as well as the growth of the local ordered regions proceeds stepwise. The crystal structure of the rotator phase of n-alkanes, which are typical of short polymer chains with simple chemical structure, has been extensively studied by experiments [1][2][3][4][5][6][7][8][9], theoretical analyses [10,11], and computer simulations [12][13][14][15][16][17][18]. Several experimental techniques including x-ray diffraction [1][2][3][4], infrared and Raman spectroscopy [5,6], neutron scattering [7,8], and NMR [9] have been used to reveal interesting features of the molecular packing, intramolecular defects, and molecular motions in the rotator phase of n-alkanes.…”
Section: Susumu Fujiwara and Tetsuya Satomentioning
confidence: 99%